Sosialisasi Penyuluh Agama Islam Guna Pencegahan Penggunaan Narkoba Terhadap Remaja dikecamatan Besitang - Wahyu Ziaulhaq (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study describes the socialization of Islamic religious educators to prevent drug use against adolescents in Besitang district. The purpose of this study is to educate readers that socialization has great benefits for drug prevention. This type of research is a qualitative research that seeks to explain the social phenomena that are developing in the current mass and then described, the results of this study are first, socialization to adolescents with religious languages ​​with a persuasive and humanist approach. Second, teenagers carry out useful activities such as attending lectures at mosques or in Islamic teaching centers, doing sports and also honing art skills. Third, the family plays a role in supervising their children and other family members.